2017
DOI: 10.1007/s12024-017-9930-1
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial adipose tissue volume estimation by postmortem computed tomography of eviscerated hearts

Abstract: Epicardial adipose tissue (EAT) may play a role in the development of coronary artery disease. The purpose of this study was to evaluate a method based on postmortem computed tomography (PMCT) for the estimation of EAT volume. We PMCT-scanned the eviscerated hearts of 144 deceased individuals, who underwent a medicolegal autopsy. Using Mimics® we performed segmentation of the images and obtained the volumes of EAT and myocardium. Total heart volume was calculated by adding the volumes of EAT and myocardium. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 12 publications
1
3
0
Order By: Relevance
“…Differences between our estimates and those of Eisenberg are quite large and probably not fully explained by the omission of the most inferior part of the epicardial tissue in their work. An interesting work by Hindsø 31 reports EATV from forensic autopsy material and again shows substantially lower EATV than in our current report, despite similar weight and BMI. The degree to which post mortem data on EATV can be compared to in vivo data is not known.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Differences between our estimates and those of Eisenberg are quite large and probably not fully explained by the omission of the most inferior part of the epicardial tissue in their work. An interesting work by Hindsø 31 reports EATV from forensic autopsy material and again shows substantially lower EATV than in our current report, despite similar weight and BMI. The degree to which post mortem data on EATV can be compared to in vivo data is not known.…”
Section: Discussionsupporting
confidence: 57%
“…The majority of works employ semi-automated methods for EAT quantification (weighted average 99.1 ml), whereas the two publications relying on automated quantification show among the lowest amounts of EATV. One publication on necropsy material 31 containing no other adipose tissue than EAT shows the lowest EATV, slightly below 70 ml, when male and female subjects are pooled.…”
Section: Resultsmentioning
confidence: 97%
“…One person conducted the manual segmentation and this is a limitation. However, CTR measurements and volumetric organ measurements have shown high interrater agreements [2,3,6,30,31]. Secondly, not all possible causes of death were assessed and hypothermia group was very small so the two hypothermia cases which fulfilled the inclusion criteria had to be excluded from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Post-mortem imaging applied to single organs or structures (X-ray, CT, MR, angiography, eventually with casts) is frequently involved in forensic pathology and may also give further information about anatomy. Hindso et al [ 85 ] demonstrated the accuracy of post-mortem CT for the measurement of the volumes of epicardial adipose tissue and myocardium in eviscerated hearts. In addition, post-mortem imaging of explanted larynxes after forensic autopsy have been proposed [ 86 ] and in a forensic case we involved post-mortem CT for better detailing of a laryngeal anatomical variation (differential diagnosis with traumatic finding) [ 87 ].…”
Section: Clinical Anatomy In Medical Malpractice Analysis—methodologi...mentioning
confidence: 99%